2007
DOI: 10.1093/molbev/msm200
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 1 Genes in Early Deuterostomes (Tunicates and Sea Urchins) and Vertebrates (Chicken and Frog): Origin and Diversification of the CYP1 Gene Family

Abstract: Cytochrome P450 family 1 (CYP1) proteins are important in a large number of toxicological processes. CYP1A and CYP1B genes are well known in mammals, but the evolutionary history of the CYP1 family as a whole is obscure; that history may provide insight into endogenous functions of CYP1 enzymes. Here, we identify CYP1-like genes in early deuterostomes (tunicates and echinoderms), and several new CYP1 genes in vertebrates (chicken, Gallus gallus and frog, Xenopus tropicalis). Profile hidden Markov models (HMMs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 73 publications
3
77
0
Order By: Relevance
“…While evidence of deuterostome (e.g. tunicate and sea urchin) CYPlA-like and CYP1-like genes exists (Goldstone et al 2007), to date no full-length CYP -like sequences have been reported for molluscs (Rewitz et al 2006) or any other protostome, further suggesting that the CYP 1 family may be deuterostome specific. Recent work by Grosvik et al (2006) strengthens this argument by calling into question immunochemical evidence suggesting the presence of a CYP 1A-like protein in molluscs.…”
Section: Pseudopterogorgia Americana)mentioning
confidence: 99%
“…While evidence of deuterostome (e.g. tunicate and sea urchin) CYPlA-like and CYP1-like genes exists (Goldstone et al 2007), to date no full-length CYP -like sequences have been reported for molluscs (Rewitz et al 2006) or any other protostome, further suggesting that the CYP 1 family may be deuterostome specific. Recent work by Grosvik et al (2006) strengthens this argument by calling into question immunochemical evidence suggesting the presence of a CYP 1A-like protein in molluscs.…”
Section: Pseudopterogorgia Americana)mentioning
confidence: 99%
“…This receptor, which is activated by small molecules and by light, is one of the 34 known proteins that both contain a PerArnt-Sim domain and regulate responses to environmental changes (1)(2)(3)(4). Both AHR itself and the first family of cytochrome P450 (CYP1) enzymes, whose expression is regulated by AHR, have been highly conserved during evolution (5,6). This observation, together with its presence in most cell types and during all phases of development, indicate strongly that, in addition to responses to xenobiotics, the AHR and its endogenous activators are involved in vital physiological processes.…”
mentioning
confidence: 99%
“…Mammalian species contain only the CYP1A and 1B subfamilies, and the CYP1C subfamily has only been identified in non-mammilian vertebrates (Goldstone et al, 2007). CYP1D1 was first identified in fish , and recently has been found in cynomolgus monkey (Uno et al, 2011).…”
Section: Cyp1 Evolution and Functionmentioning
confidence: 99%
“…Most notably, the CYP1C subfamily is not present in mammals but has been identified in frogs (Jonsson et al, 2011), birds (Goldstone et al, 2007), and fish (Zanette et al, 2009). There is only one isoform in the CYP1A family in fish and this gene (CYP1A) has the rare nomenclature such that the CYP has not been provided a gene number.…”
Section: Cyp1 Evolution and Functionmentioning
confidence: 99%
See 1 more Smart Citation